2018
DOI: 10.4103/aja.aja_19_17
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA damage has a negative effect on early embryonic development following in vitro fertilization

Abstract: Sperm DNA damage is recognized as an important biomarker of male infertility. To investigate this, sperm DNA damage was assessed by the sperm chromatin dispersion (SCD) test in semen and motile spermatozoa harvested by combined density gradient centrifugation (DGC) and swim-up in 161 couples undergoing in vitro fertilization (IVF). Semen analysis and sperm DNA damage results were compared between couples who did or did not achieve pregnancy. The sperm DNA damage level was significantly different between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
55
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 34 publications
8
55
0
1
Order By: Relevance
“…This is consistent with the results of a recent study, which showed that paternal age had no impact on fertilization rate in an IVF program (Wu et al 2015). However, since sperm DFI has been reported to be a good predictor for embryo quality (Tandara et al 2014;Zheng et al 2018), our result further indicated that sperm of aged men may still retain the ability to fertilize the oocyte but are diminished in ability to support the subsequent embryo development.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the results of a recent study, which showed that paternal age had no impact on fertilization rate in an IVF program (Wu et al 2015). However, since sperm DFI has been reported to be a good predictor for embryo quality (Tandara et al 2014;Zheng et al 2018), our result further indicated that sperm of aged men may still retain the ability to fertilize the oocyte but are diminished in ability to support the subsequent embryo development.…”
Section: Discussionsupporting
confidence: 92%
“…Although the traditional semen parameters were helpful to assess the ability of spermatogenesis and sperm maturation, the discriminative power of traditional SA is often considered to be insufficient (Oehninger et al 2014;Zhu et al 2016). DFI were considered to be a good predictor for pregnancy and miscarriage (Simon et al 2017;Zheng et al 2018); The AR test is helpful to estimate the sperm fertilization ability; and sperm vitality is a good test to exam the sperm viability (World Health Organization 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, conflicting results have been presented in the literature regarding the relationship of DNA fragmentation measured by either technique and the various end‐points measured: fertilisation, blastocyst rate, early pregnancy diagnosis, birth rate or the possible complications that sometimes occur (abortion, miscarriage, etc). Some studies praise the SCSA for their prognostic value (Evenson, ; Evenson et al, ) while others do the same for the SCD (Comhaire, Messiaen, & Decleer, ; FernĂĄndez, Cajigal, LĂłpez‐FernĂĄndez, & GosĂĄlvez, ; Pregl Breznik, Kovačič, & Vlaisavljević, ; Zheng et al, ). Caution has been recommended when considering prognosis after IVF or ICSI using solely DNA fragmentation (Anifandis et al, ; Cissen et al, ; Erenpreiss, Spano, Erenpreisa, Bungum, & Giwercman, ; Zhang et al, ) particularly when colloid gradients are used since other methods for sperm selection are more valuable, as swim‐up (Zandieh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that sperm with a high level of DFI negatively correlated with the outcomes of IVF-ET 18,23 . However, the findings from other studies suggested that DFI was not able to predict the outcomes of IVF [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies correlating the mechanical stress of sperm with embryo development are lacking. Although it has been demonstrated that sperm processing by DGC and SU is effective at reducing sperm with DNA damage, which is thought to definitely adversely affect early embryo development, it remains elusive whether a second DGC will introduce new damage to sperm, thereby finally impairing embryo development 17,18 .…”
mentioning
confidence: 99%